Promoting industrialisation in Mauritius, South Africa and Botswana : lessons for the future - Moyo, Theresa (Council for the Development of Social Science Research in Africa, 2017, 2016)
The industrialisation agenda is a topical issue in debates on Africa’s development. Evidence shows that since the 1990s, Africa has experienced de-industrialisation and consequently, the continent has the lowest Manufacturing Value Added (MVA) compared to all other regions in the world. This article argues that industrialisation must be a top priority on the agenda of development planning and management in Africa. The article is futuristic in that it focuses on strategies to promote industrialisation. It reviews and analyses the experiences of three African countries, namely, Mauritius, South Africa and Botswana. They are selected not because they have achieved the ultimate goal of industrialisation, but rather because they have taken major steps that promise to yield success in the future. The article is based on a review of secondary information such as government policy and strategy documents, published journals and other peer-reviewed literature. The analysis highlights the important role played by a strong developmental state, formulation and implementation of long-term industrial strategic frameworks, creation of effective institutions, re-introduction of industrial policies and incentives, and foreign direct investment. While recognising the historical limitations of FDI, it still recommends intensification of such investments albeit within a new framework in which governments have to negotiate better terms of engagement in order to ensure technology and skills transfer. The article also emphasizes that there is no one-size-fits-all and so each country has to develop industrialisation strategies which are appropriate to its own environment and context.
Journal article published Africa Development, Volume XLI, No. 3, 2016, pp. 139-163
Keywords: Industrialisation; Industrialisation -- Africa; Economic development projects -- Africa; Rural development